Ancestry and development: New evidence. (3rd June 2018) - Spolaore, Enrico; Wacziarg, Romain
Summary: We revisit the relationship between ancestral distance and barriers to the diffusion of development by replicating previous results with a new genomic dataset on human microsatellite variation. We find a statistically and economically significant effect of ancestral distance from the technological frontier on income per capita. The historical pattern of the effect is hump shaped, peaking between 1870 and 1913, and declining steeply afterwards. This suggests that ancestral distance acts as a temporary barrier to the diffusion of development. We also find that ancestral distance from the frontier is a barrier to the spread of specific technologies and institutions in modern times.